2011
DOI: 10.9738/1404.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phaleria Macrocarpa Supplementation on Apoptosis and Tumor Growth of C3H Mice With Breast Cancer Under Treatment With Adriamycin–Cyclophosphamide

Abstract: The objective of this study was to know the response of supplementation of Phaleria macrocarpa (PM) to adriamycin-cyclophosphamide (AC) in the treatment of C3H mice with breast cancer. Twenty-four C3H mice, who were successfully inoculated with breast cancer cells, were randomly allocated into 4 groups: without treatment, treated with AC, treated with AC + PM 0.07 mg/d, and treated with AC + PM 0.14 mg/d. The tumor size was measured using millimeter calipers before and 12 weeks after treatment. The tumor, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
(7 reference statements)
1
10
0
2
Order By: Relevance
“…The fruit is green before ripening and red when fully ripe [8]. P. macrocarpa has been used to treat cancer, diabetes, ulcers and hypercholesterolemia [9][10][11][12]. Previous studies reported the isolation of many active compounds from various parts of P. macrocarpa, including phalerin, mangiferin, benzophenone glucopyranosides, mahkoside, kaempferol-3-O-β-D-glucoside, dodecanoic acid, and palmitic acid [13].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit is green before ripening and red when fully ripe [8]. P. macrocarpa has been used to treat cancer, diabetes, ulcers and hypercholesterolemia [9][10][11][12]. Previous studies reported the isolation of many active compounds from various parts of P. macrocarpa, including phalerin, mangiferin, benzophenone glucopyranosides, mahkoside, kaempferol-3-O-β-D-glucoside, dodecanoic acid, and palmitic acid [13].…”
Section: Introductionmentioning
confidence: 99%
“…After 7 days of weekly-administered doxorubicin (2 mg/kg by intravenous injection, a classical method of chemotherapy administration), they evaluated tumour growth; significant differences were observed in the tumour volume of animals receiving doxorubicin compared with that of control animals. Another study from Riwanto et al [38] found a reduction of tumour growth in C3H mice that were inoculated with breast cancer cells and that were treated intravenously with 0.013 mg of cyclophosphamide plus 0.0156 mg of doxorubicin. Here is necessary to talk about why not differences were found in the reduction of the tumour volume after treatment of chemotherapy alone or in combination with Maitake D-Fraction Pro4X.…”
Section: Discussionmentioning
confidence: 99%
“…From leaves to root, every part of P. macrocarpa plants (leaves, bark , stem , seed and fruit) is being used as a traditional medicine for different types of cancer especially against breast cancer and brain tumor . Phaleria macrocarpa is also used as a supplement with adriamycin cyclophosphamide (AC) for reducing tumor growth in breast cells by inducing apoptosis and at the same time, it protects liver and kidney from damage caused by AC . Phalerin and gallic acid has a major contribution in its cytotoxic properties .…”
Section: Biological Activitymentioning
confidence: 99%